2015
DOI: 10.1039/c5ra05986k
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the temperature sensing behavior of Yb3+ sensitized Er3+ doped Y2O3, YAG and LaAlO3 phosphors

Abstract: The sensitivities (S) of Y2O3 (YAG/LaAlO3):Yb3+/Er3+ phosphors increased with increasing average bond covalency and the calculated values were basically in good agreement with our experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Wei et al revealed that the maximum sensor sensitivity of Bi 4 Ti 3 O 12 :Er 3+ nanoparticles was around 0.0043 K −1 in the operating temperature range of 115–490 K . Kumar and co‐workers demonstrated that the CaMoO 4 :Er 3+ /Yb 3+ upconverting nanoparticles were suitable for high‐temperature measurement with a maximum sensor sensitivity of around 0.00532 K −1 . Clearly, the sensor sensitivities of the previous developed optical temperature sensors are still not high enough for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al revealed that the maximum sensor sensitivity of Bi 4 Ti 3 O 12 :Er 3+ nanoparticles was around 0.0043 K −1 in the operating temperature range of 115–490 K . Kumar and co‐workers demonstrated that the CaMoO 4 :Er 3+ /Yb 3+ upconverting nanoparticles were suitable for high‐temperature measurement with a maximum sensor sensitivity of around 0.00532 K −1 . Clearly, the sensor sensitivities of the previous developed optical temperature sensors are still not high enough for practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence‐based thermometers have garnered lots of attention in view of their unique advantages, such as good accuracy, high sensitivity, and fast response . Recently, a large number of interests have been sparked on optical thermometry based on fluorescence intensity ratio (FIR) method derived from thermally coupled energy levels (TCEL) .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a large number of interests have been sparked on optical thermometry based on fluorescence intensity ratio (FIR) method derived from thermally coupled energy levels (TCEL) . Compared to other fluorescence‐based thermometry (such as fluorescence intensity, fluorescence lifetime, and peak position), optical thermometry using FIR method with better antijamming capability and improved sensitivity is considered as a promising approach for optical thermometers . Operating as “non‐contact”, such optical thermometry is particularly favorable for the temperature measurement in electromagnetically and thermal harsh environment, such as building fire detections, biological imaging systems, and micro/nanoscale temperature measurement …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the fluorides, Y 2 O 3 has the advantages of a high melting point, wide bandgap, high solubility between Y 3+ and Er 3+ , and good transparency in ultraviolet and infrared range 27 . Based on the green emissions from thermally coupled energy levels of 2 H 11/2 and 4 S 3/2 , the optical temperature sensing was studied in Er 3+ -Yb 3+ co-doped Y 2 O 3 bulks and nano-materials 2732 . However, the aforementioned works have not dealt with excitation powers dependent optical temperature sensitivity, and lack to explore how to improve the optical temperature behaviors.…”
Section: Introductionmentioning
confidence: 99%